Hairy cell leukemia: a histo-cytochemical and ultra-structural study - Gonsalez, Denise; Oliveira, José Salvador Rodrigues; Haapalainen, Edna; Kerbauy, José (São Paulo Medical Journal, 1998)
We studied five patients with hairy cell leukemia (HCL) diagnosed within the last ten years at the Department of Hematology of Universidade Federal de São Paulo - Escola Paulista de Medicina. Our purpose was to analyze the value of transmission electron microscopy (TEM) by comparing this method with the conventional ones. At diagnosis, patients presented weight loss, spleen enlargement and hairy cells (HC) in peripheral blood and bone marrow slides. HC was characterized by morphology and tartrate test resistance in the acid phosphatase reaction (TRAP). At the evaluation time, the amount of HC ranged from 1% to 85% of WBC count. All patients, except two, had phenotype B. In these last two, TRAP as well as phenotype B could not be documented due to low HC numbers in their exams. Cytoplasmatic projections and the absence of lamellar ribosomic complex were the most frequent ultrastructural findings, even in those patients with the lowest HC numbers. Based on these features, TEM is an efficient method for searching for HC at HCL diagnosis and during the course of the disease.